Prevalence and Management of Multiple Valvular Heart Disease in Patients Undergoing Transcatheter Aortic Valve Replacement: A Multicenter Study on the Impact of Staged Valvular Interventions on Outcomes - Baravan Al‐Kassou; Jannik Kapplinghaus; Caroline Meckelburg; Jasmin Shamekhi; Adem Aksoy; Hendrik Wienemann; Lara Al‐Kassou; Andreas Zietzer; Atsushi Sugiura; Vedat Tiyerili; Clemens Eckel; Johanna Vogelhuber; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Multiple valvular heart disease correlates with poor outcomes following transcatheter aortic valve replacement. Previous studies have focused on mitral regurgitation (MR) or tricuspid regurgitation (TR) individually, without comparing their long‐term effects. The impact of staged transcatheter edge‐to‐edge repair (TEER) remains unclear. We aimed to assess the prevalence and effects of severe multiple valvular heart disease (sMVHD) and evaluate the impact of staged TEER on outcomes. Methods Patients were recruited from 4 transcatheter aortic valve replacement centers. The primary cohort included 2823 patients to evaluate the prevalence of sMVHD. All patients were screened for additional valvular interventions; those undergoing TEER for severe MR (n=147) or TR (n=59) were included. Results Concomitant sMVHD was observed in 369 patients, with 208 having severe MR and 161 having severe TR. The 1‐year mortality rate was higher in patients with sMVHD compared with the overall cohort (9.0 versus 5.2 per 100 person‐years; P<0.01). Severe TR was associated with the highest 1‐year mortality rate, followed by severe MR and no or mild multiple valvular heart disease (13.3 versus 6.4 versus 3.9 per 100 person‐years; P<0.01). This difference persisted over 5 years (P<0.01). Patients undergoing staged TEER showed a reduced 1‐year mortality rate compared with conservative management (4.1 versus 12.1 per 100 person‐years; P<0.001). This trend continued over 5 years (P<0.001). Severe TR was independently associated with an increased mortality rate (hazard ratio, 1.79 [95% CI, 1.17–2.74]; P<0.01). Conclusions Persistent sMVHD was associated with an increased mortality rate following transcatheter aortic valve replacement, with severe TR posing a higher risk than severe MR. Staged TEER was associated with improved outcomes and warrants consideration in sMVHD.